A new form of the psychometric function for the unspecified tetrad. (June 2020) - Bi, Jian
Highlights: A new form of the psychometric function for the unspecified tetrad is provided. The new form of the psychometric function is based on a noncentral F distribution. The new form of the psychometric function has practical and theoretical values. Abstract: The tetrad is a popular sensory discrimination method used widely in the sensory and consumer fields. This short communication provides a novel, concise, and elegant form of the psychometric function based on a noncentral F distribution for the unspecified tetrad. The new form of the psychometric function for the unspecified tetrad has practical and theoretical values.